What factors are Associated with the Development of Contras-induced Nephropathy in Elderly Patients with Acute Coronary Syndrome in Real Clinical Practice? - M. Yu. Gilyarov; E. V. Konstantinova; P. V. Kovalets; A. V. Slivin; A. E. Udovichenko; A. P. Nesterov; O. N. Svetlova; A. V. Svet (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To study the factors associated with contrast-induced acute kidney injury in elderly patients with acute coronary syndrome (ACS).Material and Methods. A retrospective analysis of 514 electronic medical records of patients aged 75 years and over (38% men and 62% women) with confirmed acute coronary syndrome has been performed. The contrast-induced acute kidney injury was defined as an increase in serum creatinine ≥26.5 μmol/L in 48 h or as an increase in serum creatinine in 1.5 times within 7 days after the contrast media exposure. Patients were divided into contrast-induced acute kidney injury and non-contrast-induced acute kidney injury group. Clinical characteristics and in-hospital outcomes were extracted from patients' medical records. Procedural characteristics were obtained from laboratory database.Results. Angiographic intervention was performed in 74% of patients, 32% of them (more often in women, p=0.033) were diagnosed with contrast-induced acute kidney injury. Patients with contrast-induced acute kidney injury are characterized by a higher death rate (17% и 3%, p<0.001) and were more likely to have heart failure with reduced ejection fraction (34% и 21%, p=0.008) and acute heart failure (Killip class II-IV) (24% и 16%, p=0.015). The risk of developing contrast-induced acute kidney injury was related the volume of contrast medium administered.Conclusions. Prevention particular care should be taken to female patients older than 75 years with ACS, with a history of the chronic heart failure with reduced ejection fraction or acute heart failure (Killip class II-IV), and with a high volume of contrast media, highlighting that a perioperative comprehensive management strategy is needed to improve the prognosis.